The immigrants’ role in the female activity in Spain. a decade of economic expansion (1999-2008) - Vidal Coso, Elena; Miret Gamundi, Pau (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Using data from the Labour Force Survey (1999-2008) this paper analyzes the existing differences between the labour participation trends of native and immigrant women, considering the strong relationship between productive and reproductivework. The hypothesis is that, in a labour market thatis segmented by gender and migrant origin, individual characteristics (age, educational attainment), family characteristics (partnership,dependent children and partner’s occupational status) and, specifi cally for immigrant women, the migratory strategy (who is the pioneer of the family migration, years from migrations) influence the female participation rates differently in accordance with the region of origin. Whilst the activity of native women is clearly explained by age and educational level, participation patterns of immigrant women are more determined by their family characteristics and their migratory histories. Moreover,results indicate a diverse range of immigrant participationpatterns based on a women’s region of birth. African women havea weak labour participation, very infl uenced by their family characteristicsand by the length of the settlement from migration.Conversely, Latin American and non-EU women present higher participation rates than native women at all active age groups,independently of their educational attainment.
Keywords: Activity; Gender; Conciliatory strategies; Labour segmentation; Migratory Experience.